2023
DOI: 10.1101/2023.01.20.524919
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Microbial methane cycling in a landfill on a decadal time scale

Abstract: Landfills generate outsized environmental footprints due to microbial degradation of organic matter in municipal solid waste, which produces the potent greenhouse gas methane. With global solid waste production predicted to increase 69% by the year 2050, there is a pressing need to better understand the biogeochemical processes that control microbial methane cycling in landfills. In this study, we had the rare opportunity to characterize the microbial community responsible for methane cycling in landfill waste… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 95 publications
0
8
0
Order By: Relevance
“…The public datasets in which giant proteins were detected were from landfill leachate metagenomes (Grégoire et al 2023) , anaerobic digester sludge in the United States (Mei and Liu 2022) and China (Liu et al 2021) , lake water in Spain (Cabello-Yeves et al 2022) and Finland (Buck et al 2021) , subsurface fracture fluids (Casar et al 2021) in the United States, groundwater in New Zealand (Mosley et al 2022) and Finland (Bell et al 2022) , hydrocarbon field communities in Canada (An et al 2013) , Norwegian fjord waters (Suarez et al 2022) , river estuary sediment from China (Wang et al 2021) , magnetotactic enrichment communities (Lin et al 2020) , and a limonene enrichment from bog soil in Germany (Kizina et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The public datasets in which giant proteins were detected were from landfill leachate metagenomes (Grégoire et al 2023) , anaerobic digester sludge in the United States (Mei and Liu 2022) and China (Liu et al 2021) , lake water in Spain (Cabello-Yeves et al 2022) and Finland (Buck et al 2021) , subsurface fracture fluids (Casar et al 2021) in the United States, groundwater in New Zealand (Mosley et al 2022) and Finland (Bell et al 2022) , hydrocarbon field communities in Canada (An et al 2013) , Norwegian fjord waters (Suarez et al 2022) , river estuary sediment from China (Wang et al 2021) , magnetotactic enrichment communities (Lin et al 2020) , and a limonene enrichment from bog soil in Germany (Kizina et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen metagenomes were sequenced from an active municipal landfill and adjacent aquifer in Southern Ontario (SO), sampled twice one year apart (July 2016 [SO 2016] and October 2017 [SO 2017]) and described previously [9,35]. Nine metagenomes were from a northeastern United States active municipal landfill (NEUS) in which nine distinct cells, units in which waste is held within the landfill, were sampled in February 2019 as described previously [36]. At the time of sampling, the oldest cell had received waste from 1980 to 1982 (39 years of waste decomposition time), whereas the youngest cell began receiving waste in 2014 (5 years of waste decomposition time).…”
Section: Sampling Sites and Metagenomesmentioning
confidence: 99%
“…Sampling of the Southern Ontario (SO) landfill occurred twice one year apart (July 2016 [SO 2016] and October 2017 [SO 2017]) and has been described previously [9,35]. Nine distinct cells of the NEUS landfill were sampled in February 2019 as described previously [36]. The final four metagenomes came from a closed landfill from Southern California (CA_2019) that was sampled in June of 2019.…”
Section: Samplingmentioning
confidence: 99%
“…Studies that reported abundances found that organisms of this candidate phylum always constituted <1% of the community. Currently, there is only one Hydrogenedentota MAG available from Shark Bay (Skoog et al, 2022 ), but MAGs of Hydrogenedentota have been assembled from other environments including subsurface waters (Momper et al, 2018 ; Mosley et al, 2022 ; Tully et al, 2018 ), hot spring water and sediments (Liew et al, 2022 ; Zhou et al, 2020 ), marine sediment (Zhou, Mara, et al, 2022 ), freshwater sediment (Hahn et al, 2022 ; Jaffe et al, 2023 ), hydrothermal vents (Speth et al, 2021 ; Zhong et al, 2022 ; Zhou, St. John, et al, 2022 ), anaerobic digesters and annamox bioreactors (Campanaro et al, 2020 ; Lin et al, 2021 ; Nobu et al, 2015 ; Pabst et al, 2022 ; Rinke et al, 2013 ; Suarez et al, 2022 ; Wang et al, 2020 ; Wang et al, 2022 ; Zhang et al, 2022 ), wastewater (Grégoire et al, 2023 ; Haryono et al, 2022 ; Huang et al, 2021 ; Parks et al, 2017 ) and saline and hypersaline sediments (Uzun et al, 2020 ; Vavourakis et al, 2019 ). Of these studies, only one characterized this organism and identified Ca.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, only one Sumerlaeota MAG has been assembled from a pustular mat in Shark Bay (Skoog et al, 2022 ). MAGs of Sumerlaeota have been assembled from other environments including other hypersaline microbial mats and marine biofilms (Karačić et al, 2018 ), anaerobic digesters and anammox bioreactors (Mei, 2020 ; Suarez et al, 2022 ; Wang et al, 2020 ; Ya et al, 2022 ; Zorz, 2021 ), animal gut microbiomes (Lemos et al, 2022 ), freshwater lake water and sediment (Hahn et al, 2022 ; Jaffe et al, 2023 ; Tran et al, 2021 ), coral skeleton biofilms (Tandon et al, 2022 ), hot spring sediment and water (Fang et al, 2021 ; Kato et al, 2022 ; Liew et al, 2022 ), water and sediments around a hydrothermal vent (Speth et al, 2021 ; Zhong et al, 2022 ), marine, saline, and hypersaline sediments (Baker et al, 2015 ; Fang et al, 2021 ; Rinke et al, 2013 ; Vavourakis et al, 2019 ; Zhou, Mara, et al, 2022 ), subsurface water (He et al, 2020 ; Hernsdorf et al, 2017 ; Kadnikov et al, 2019 ), soil (Parks et al, 2018 ), wastewater (Haryono et al, 2022 ; Huang et al, 2021 ), and landfills (Grégoire et al, 2023 ). This rare candidate phylum appears to be omnipresent but is always reported at very low abundances (<1%).…”
Section: Introductionmentioning
confidence: 99%